2019
DOI: 10.1103/physreva.100.052302
|View full text |Cite|
|
Sign up to set email alerts
|

Resource-efficient analyzer of Bell and Greenberger-Horne-Zeilinger states of multiphoton systems

Abstract: We propose a resource-efficient error-rejecting entangled-state analyzer for polarization-encoded multiphoton systems. Our analyzer is based on two single-photon quantum-nondemolition detectors, where each of them is implemented with a four-level emitter (e.g., a quantum dot) coupled to a onedimensional system (such as a micropillar cavity or a photonic nanocrystal waveguide). The analyzer works in a passive way and can completely distinguish 2 n Greenberger-Horne-Zeilinger (GHZ) states of n photons without us… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 117 publications
0
19
0
Order By: Relevance
“…Multiparticle entanglement has attracted great attention for its diverse applications in quantum metrology and quantum computing [1][2][3][4][5][6][7][8][9][10]. Efforts along this direction have lead to a plenty of proposals for generating entangled states with particles as many as possible [11][12][13], such as spin squeezing states [14][15][16] and GHZ states [17][18][19][20]. So far, multiparticle entanglement has been realized involving up to 20 qubits in trapped-ion systems [21], and 12 qubits in superconducting circuits [22].…”
Section: Introductionmentioning
confidence: 99%
“…Multiparticle entanglement has attracted great attention for its diverse applications in quantum metrology and quantum computing [1][2][3][4][5][6][7][8][9][10]. Efforts along this direction have lead to a plenty of proposals for generating entangled states with particles as many as possible [11][12][13], such as spin squeezing states [14][15][16] and GHZ states [17][18][19][20]. So far, multiparticle entanglement has been realized involving up to 20 qubits in trapped-ion systems [21], and 12 qubits in superconducting circuits [22].…”
Section: Introductionmentioning
confidence: 99%
“…They also showed that this result has potential applications ranging from optical quantum information processing to QND photon‐number measurements 57 . In addition, some attractive PPC gates based on other nonlinear optical elements have also been proposed, such as those involving quantum‐dot spins in optical microcavities 58‐61 . For example, in 2019, Li et al proposed an error‐rejecting entangled‐state analyzer for polarization‐encoded multiphoton systems based on two single‐photon quantum‐nondemolition detectors, which can be constructed with quantum dots coupled to micropillar cavities 61 .…”
Section: Discussion and Summarymentioning
confidence: 99%
“…In addition, some attractive PPC gates based on other nonlinear optical elements have also been proposed, such as those involving quantum‐dot spins in optical microcavities 58‐61 . For example, in 2019, Li et al proposed an error‐rejecting entangled‐state analyzer for polarization‐encoded multiphoton systems based on two single‐photon quantum‐nondemolition detectors, which can be constructed with quantum dots coupled to micropillar cavities 61 . Based on above works, the PPC gate used in our protocol may be experimentally realized in the future.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…Next, we consider the distinguishment of N ‐qubit GHZ states. First of all, we define the N ‐qubit GHZ states as in 24]. For the N ‐qubit GHZ states, the simplest two are [ 16 ] truerightfalse|normalGHZ000false⟩=12false(false|0false⟩N+false|1false⟩Nfalse)12Nrightfalse|normalGHZ001false⟩=12false(false|0false⟩Nfalse|1false⟩Nfalse)12Nin which the subscript of the N th qubit refers to the phase by the symbols ± (0 refers the phase +, while 1 refers the phase −).…”
Section: Complete Distinguishment Of Ghz Statesmentioning
confidence: 99%